Hubungan Antara Tingkat Kehadiran dan Partisipasi Aktif Terhadap Minat Belajar Mahasiswa Akuntansi Syariah pada Mata Kuliah Statistika - Siregar, Rizka Fahruza (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to determine the relationship between attendance levels and active participation towards the interest and learning of students in Islamic accounting in the statistics course. This research is descriptive with a quantitative approach. Data collection was obtained through the completion of questionnaires given to respondents. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results showed a significant relationship between attendance levels, active participation, and interest in learning in the statistics course. The higher the students' attendance in class, the greater their interest in learning. This indicates that regular and active student attendance in the teaching and learning process has a positive impact on their interest in learning